Defect induced ferromagnetic ordering in epitaxial Zn0.95Mn0.05O films on sapphire (0 0 0 1). (6th September 2019) - Liu, Wei-Rein; Pao, Chih-Wen; Yu, Doris Weijyun; Chin, Yi-Ying; Wu, Wen-Bin; Lin, Hong-Ji; Haw, Shu-Chih; Chu, Chia-Hung; Chao, Tzu-Yang; Hsu, Hsu-Cheng; Chen, Jin-Ming; Hsu, Chia-Hung; et al.
Abstract: We report the influence of Mn dopant on magnetic properties of Zn0.95 Mn0.05 O (ZMO)/Al2 O3 (0 0 0 1) hetero-epitaxial systems grown by using pulsed-laser deposition. The room temperature (RT) intrinsic ferromagnetic (FM) ordering verified by superconducting quantum interference device magnetometer and x-ray magnetic circular dichroism spectrum of Mn L 2, 3 edges is ascribed to the substitutional Mn atoms in the Zn site of ZnO. Mn in ZMO has a tetrahedral local symmetry instead of the octahedral symmetry of MnO, after verifying the absence of the Mn-related impurities or clusters in ZMO epitaxial film by Mn K -edge and Zn K -edge x-ray absorption spectroscopy spectrum, as well as the analysis of long-range structural ordering on Renninger scan of forbidden (0 0 0 5) reflection in x-ray diffraction, transmission electron microscopy and Raman spectrum. Comparison of x-ray absorption spectra of ZMO with those of ZnO epilayers at O K -, Zn K -, and L 3 -edges indicates that the substitution of the Zn site with Mn enhances the charge-transfer (CT) transition and the presence of Zn vacancies (VZn ) also dominate the photoluminescence (PL) spectrum, implying that the formation of numerous VZn defects plays an important role in activating FM interactions. The strong CT effect and the existence of high-density VZn suggest that the intrinsic RT FM ordering of insulating ZMO is a result of the formation of the bound magnetic polarons (BMPs) that interact with each other via intermediate magnetic impurities.